An analysis of the portrayal of multicultural education in Zimbabwean primary school English textbooks - Mareva, Florence; Mareva, Rugare (IJRDO - Journal of Social Science and Humanities Research, 2016)
Due to the pluralistic nature of the Zimbabwean culture, English language teaching has become an instrument for effective cultural interaction between different ethnic minority groups. Therefore, content in text books should be representative of all cultures. This paper analyses the extent to which the ethnic minority groups’ cultures are represented in primary school English textbooks. The study posits that ethnic minority groups’ cultures are left out. Through a Context Analysis, the study established that ethnic minority groups’ cultures are left out and only dominant groups’ cultures take a central stage. The study recommends that various ethnic minority groups should be included in the texts to cater for multicultural education.